Sistem Informasi Pemotongan PPh 21 Atas Gaji Karyawan PT. Rajawali Tehnik - Kyky Rizky Zuana; Iwan Sidharta (Jurnal Computech & Bisnis (e-Journal), 2014)
In the era of globalization is now the technology is already familiar in our daily lives. Both are used as a means of communication, education and public facilities. In this case I do research on the administrative activities of the company, in which there are activities that will be proposed computerized into an application. The object of research is an engineering company in data processing payroll and taxes PPh 21 have not been conserved to the maximum, although it has been computerized. Thus the need for an information system that can help the company to process payroll data and the calculation of income tax in an integrated manner. One of the tools that can support this is to use a computer and adequate human resources, so that it can form a good information system. The second stage of analysis to determine the weaknesses of the system and to evaluate the results that can be performed system design. Applications aids used are Visual Basic 2005. Keywords: salary; income tax; information systems payroll and income taxes